Analysis of association of polymorphic variants of genes GSTP1 and GSTM1 with survival rate sick of liver cirrhosis of a virus and alcoholic etiology - M. I. Rachkovskiy; I. A. Goncharova; E. I. Beloborodova; Ye. V. Beloborodova; Ye. G. Gruzdeva; A. S. Alekseyeva; V. P. Puzyryov (Бюллетень сибирской медицины, 2009)
With the purpose of studying of association of polymorphic variants of genes glutathione S-transferases pi and mu (GSTP1 and GSTM1) with survival rate sick of liver cirrhosis (LC), it is lead uniinstantly research of 189 sick of LC of a virus (HBV, HCV, H V+H V) and an alcoholic etiology. Have been В С compared a frequencies of allocation of polymorphic variants of genes GSTP1 and GSTM1 between the died and persisted patients for the season 4 years. With greater survival rate of sick of LC associated: presence of genotype АА of gene GSTP1 (χ 2 Pearson, р = 0,008) and «null» genotype GSTM1 (χ 2 Pearson, р = 0,027). Chances of development of a lethal outcome at sick of LC with presence of genotypes GG and AG on gene GSTP1 in 2,5 times above, than at patients with genotype АА. Presence of active gene replica GSTM1 enlarges chances of development of a lethal outcome in 2 times. The received results testify to necessity of the count of genetical factors for the forecast of LC.